2015
DOI: 10.1002/ss.20144
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ Experiences in Curricular Contexts

Abstract: This chapter examines curricula as important microsystems for LGBTQ college students. The authors explore sociocultural influences on curricula and discuss strategies for creating positive curricular experiences for LGBTQ students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Additionally, results revealed that those in fields such as engineering and business perceived less LGBQ+ inclusion, echoing previous studies finding that certain disciplines further identityneutral practices that do not attend to LGBQ+ collegians' social identities (see Linley & Nguyen, 2015;Rankin et al, 2019).…”
Section: -Bisexual Identifying Studentsupporting
confidence: 72%
See 1 more Smart Citation
“…Additionally, results revealed that those in fields such as engineering and business perceived less LGBQ+ inclusion, echoing previous studies finding that certain disciplines further identityneutral practices that do not attend to LGBQ+ collegians' social identities (see Linley & Nguyen, 2015;Rankin et al, 2019).…”
Section: -Bisexual Identifying Studentsupporting
confidence: 72%
“…Specifically, a growing body of research named the ways that LGBQ+ individuals experience curricular spaces (e.g., Bilimoria & Stewart, 2009;Brown, Clarke, Gortmaker, & Robinson-Keilig, 2004;Hughes, 2018;Patridge, Barthelemy, & Rankin, 2014;Sevecke et al, 2015). For example, reviews of literature pertaining to LGBQ+ students regularly reveal the differences that exist across academic disciplines concerning LGBQ+ inclusion (Linley & Nguyen, 2015;Rankin, Garvey, & Duran, 2019). Studies showcase that LGBQ+ individuals frequently perceive STEM disciplines as more likely to overlook the relevance of sexuality and to render LGBQ+ issues invisible (Bilimoria & Stewart, 2009;Hughes, 2017;Patridge et al, 2014).…”
Section: Inclusive Classroom Environments and Lgbq+ Studentsmentioning
confidence: 99%
“…Scholars may feel more or less comfortable disclosing in a given department based on its perceived climate, which varies. Linley and Nguyen () find that LGBTQ students typically rate STEM disciplines as less open to their identities. Finally, at the individual level, professors cultivate their own gendered practices.…”
Section: Disclosing Trans Identitiesmentioning
confidence: 99%
“…Oppressive campus climates decrease LGBTQ student engagement in both curricular and cocurricular involvements (Bazarsky, Morrow, & Javier, ; Linley & Nguyen, ). Previous scholars have documented the negative climate experiences that LGBTQ students face in Greek organizations (Case, Hesp, & Eberly, ; Hesp & Brooks, ), athletics (Worthen, ), and religious organizations (Stewart & Gold, ).…”
Section: Campus Climate For Lgbtq Studentsmentioning
confidence: 99%
“…Previous scholars have documented the negative climate experiences that LGBTQ students face in Greek organizations (Case, Hesp, & Eberly, ; Hesp & Brooks, ), athletics (Worthen, ), and religious organizations (Stewart & Gold, ). Chilly campus climates may discourage LGBTQ undergraduate students from feeling attached to their learning experience (Renn, ) because they may feel invisible and underrepresented in the academic environment (Gortmaker & Brown, ; Linley & Nguyen, ). Disparities in climate perceptions and experiences may prevent LGBTQ students from achieving successful academic and social outcomes because students who endure harassment and/or victimization on campus are less likely to experience success (Vaccaro, ).…”
Section: Campus Climate For Lgbtq Studentsmentioning
confidence: 99%